Mortality of dogs and cats in the transoperative and postoperative period: Retrospective study - Soares, Thais Jassek; Carareto, Roberta; Shiguihara, Danielle; Barazetti, Laura; Matos de Rezende, Leticia; Severiano, Maritza Nunes (Pubvet, 2022)
The present study aims to carry out a retrospective study of the mortality rate of dogs and cats submitted to general anesthesia for more than 30 minutes at the Veterinary Hospital of the Federal University of Paraná, Curitiba/PR Campus, between January 2011 and December 2016, totalizing 1,729 anesthetic records evaluated. This retrospective is of very importance to obtain results about the success rate of anesthetic protocols performed on dogs and cats by residents and teachers. During the study, the following data were collected: race, age, ASA, type of procedure, death, time of death, anesthetic protocol with pre-anesthetic medication, induction and maintenance. The mortality rate was 1.16%. The statistical analysis showed a correlation between the ASA classification and the occurrence of deaths, showing the importance of the patient's ASA classification to establish the anesthetic risk.
Keywords: Anesthesiology; death; veterinary